Surgery of the craniovertebral junction - Bambakidis, Nicholas C. (Thieme, 2012)
The original and definitive reference on surgery of the craniovertebral junction, now in an updated second edition. The craniovertebral junction, with a significant range of pathologies and anatomical complexities, continues to be a challenging area for surgeons. This new edition of Surgery of the Craniovertebral Junction focuses on surgical decision making and technological advances in the treatment modalities for this region. Written and edited by senior surgeons at University Hospitals Case Medical Center in Cleveland, Ohio, and the world-renowne.